EPISTOMOLOGICAL APPROACH AND FIQH TEACHING: BAYANI, BURHANI AND IRFANI CONCEPTS APPLIED AT THE TERTIARY LEVEL - Nurhadi (Program Studi Manajemen Pendidikan Islam, 2026)
This research aims to explain the concepts of bayani, burhani and irfani which are integrated into fiqh learning in the Al-Islam muhammadiyahan course at UMJ. This research method uses descriptive analysis taken based on data in the field through references obtained from Manhaj Tarjih, and more specifically on the concepts of bayani, burhani and irfani. This research has its object at Muhammadiyah University, Jakarta. And involves various data collection techniques such as analysis and interviews with expert Bayani, Burhani and Irfani informants. As well as a review of previous research findings. The collected data was analyzed using various data reduction, presentation and verification. The findings of this research suggest that the application of the bayani, burhani and irfani approaches in learning Fiqh in the Al-Islam Kemuhammadiyahan aspect of worship has not been fully implemented. The importance of applying the concepts of bayani, burhani, and irfani in learning fiqh in tertiary institutions is highlighted in this research. Further research can determine the impact of implementing learning other than fiqh in higher education on the concepts of bayani, burhani and irfani. This research provides unique insight into the results that can be used as input through future research in the field of education in higher education which originates from the application of the concepts of bayani, burhani, and irfani.